Comparative Analysis of the Income of Contract and Non-Contract Tomato Farmers in Ankpa Local Government Area of Kogi State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
This study examined effect of contract farming on the income of Tomato farmers in Ankpa Local Government Area of Kogi State. Multistage sampling technique was used to collect sample of 150 tomato farmers (75 farmers for each of contract and non-contract farmers). Primary data used for the study were collected using a structured questionnaire administered to the respondents. Data were analysed using Descriptive Statistics, T-test of Mean Difference and Gross Margin Analysis. Results showed that majority (74.67%) of the respondents were males. Average age was 33 years. About 47% of the respondents were married. Average household size was 9 persons. Average farming experience and farm size were 11 years and 5 hectares respectively. The Gross Margin of contract farmers was N375, 174 while that of non-contract farmers was N303, 950. The mean income of contract farmers was N5, 120 while that of non-contract farmers was N3, 350. The probability value of t (0.000) being less than 0.05 alpha level showed that there was a significant difference between the income of contract and non-contract tomato farmers. It was discovered that contract farmers earned more income than non-contract farmers. Non-contract tomato farmers should venture into contract farming so as to benefit from the contracting individuals or firms who supply farm input to contract tomato farmers.
Keywords: Contract; Farming; Effect; Income; Non-contract